(untitled) (Journal of Asian Development Studies, 2015)
This purpose of this study to elaborate that how can police department officers will be motivated who are not promoted in their prolonged career and also examine the affect of retention, job rotation and satisfaction on employee motivation. The proposition statement of this study had been developed on the basis of past literature & some theories and tests these statements by using correlation and regression analysis techniques. The data was collected from different police un-promoted police officers who are doing job in departments of Islamabad, Pakistan. The study results shown all the study hypothesis significantly confirmed. This paper concluded that HR police departments should be focused on this theme that how can motivate the un-promoted police officers through job enlargement and rotation and also retain the employees for increasing their commitment level and honestly performing job. This study help the HR for this matter which ultimately pursue to control the corruption which strongly existed in these type of departments as well this study can be applicable in military and other security departments.